Transformative Leadership Model of PAI Teachers as an Effort to Achieve Memorization Quality Target - Mafazatun Nafsiah; Djamaluddin Perawironegoro; Rika Astari; Suyadi Suyadi (Journal of Indonesian Progressive Education, 2025)
This study was motivated by a 14.11% decline in students’ Qur’an memorisation quality at SMAIT Bina Umat Yogyakarta over the past three academic years, which was associated with below-standard reading proficiency, conventional instructional approaches, and limited optimisation of Islamic Education (PAI) teachers’ leadership in mentoring activities. This study aimed to formulate and analyse a transformational leadership model of PAI teachers as a strategic effort to achieve memorisation quality targets. A qualitative approach with a case study design was employed. The research subjects consisted of six PAI teachers and six students. Data were collected through in-depth interviews, participatory observation, and document analysis, and analysed through data reduction, data display, and conclusion drawing. The findings reveal a transformational leadership model characterised by exemplary influence, Inspirational Motivation, intellectual stimulation, and Individualized Consideration integrated into spiritual mentoring practices. The model strengthens students’ commitment, learning discipline, and memorisation strategies. Students’ memorisation quality generally met institutional standards, including tajwid accuracy, articulation, reading fluency, and a minimum memorisation target of 1.5 juz annually. Leadership practices demonstrated measurable improvement in memorisation outcomes, with reading fluency achievement ranging from 88% to 98% of students. The study concludes that the transformational leadership model is an effective strategic approach for achieving sustainable targets for memorisation quality.